KNOWLEDGE OF GENERAL DOCTORS OF PRIMARY HEALTH SERVICE FACILITIES IN SEMARANG CITY ABOUT DEMENTIA IN SEMARANG CITY - Arinta Puspita Wati; Hexanto Muhartomo; Fatiha Sri Utami Tamad; Retna Putri (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Background. Dementia is a syndrome due to brain disease, usually chronic or progressive and there is a disturbance of sublime function. Lack of knowledge and awareness of health workers about the occurrence of dementia can worsen dementia due to delays in diagnosis and treatment. Method. This study is a descriptive study with a cross sectional design involving 66 respondents who have agreed to the informed consent and are general practitioners who work in Primary Health Care Facilities. Sampling using consecutive sampling technique, samples that meet the inclusion and exclusion criteria. Data collection was carried out in November 2021. Data analysis used SPSS 22.0 ver. Results. The average knowledge of respondents before the training was described from the pretest score of 5.2. Conclusion. Lack of knowledge about dementia in general practitioners who work in primary health care facilities in the Semarang.